Analyzing the Meaning of Idiomatic Expressions in Adele’s 21 Album - Hidayah Mudzaki Wiranda; Muhammad Ilham; Nurul Fadhilah (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The focus of this study was to examine the idiomatic expressions present in Adele’s 21 album. The research aimed to identify and analyze the different types of idiomatic expressions used in the album, as well as provide a semantic analysis of these expressions. The main objective was to gain a better understanding of the types of idiomatic expressions and their meanings in Adele’s 21. The study utilized the Makkai theory, which focuses on English idioms in the album. The data was collected by reading, identifying, analyzing, and interpreting the phrases, words, and collocations found in the songs. The data was then analyzed using Makkai’s theories to identify any issues in the analysis. The study found a total of 31 idioms in the songs, which were classified into four types of idioms offered by Makkai, including six phrasal verb idioms, one phrasal compound idiom, and no tournure or incorporating idioms. The semantic analysis revealed that the 31 idioms corresponded to five types of meaning found in Adele’s 21 album, according to Leech’s theory.